Marxisms in the 21st Century Crisis, critique and struggle - Bond, Patrick (Wits University Press, 2013)
The current resurgence of Marxism is based on new sources of inspiration and creativity from movements that seek democratic, egalitarian and ecological alternatives to capitalism. The Marxism of many of these movements is neither dogmatic nor prescriptive, but rather, open, searching, utopian. It revolves around four primary factors: the importance of democracy for an emancipatory project; the ecological limits of capitalism; the crisis of global capitalism; and the learning of lessons from the failures of Marxist-inspired experiments. Marxisms in the Twenty-First Century challenges vanguardist Marxism featured in South Africa and beyond. Featuring leading thinkers from the Left, the book offers provocative ideas on interpreting our current world and serves as an excellent introduction to new ways of thinking about Marxism to students and scholars in the field. Many anti-capitalist traditions and themes - including democracy, globalisation, feminism, critique and ecology inform and shape the contributions in this volume.